THE IMPACT OF SOCIAL COMPARISON ON INSTAGRAM WITH BODY IMAGE ESTABELISMENT IN YOUNG ADULTS - Kinanthi Riandifa; Kezia Arum Sary; Kheyene Molekandella Boer; Nurliah (International Journal of Cultural and Social Science, 2025)
The purpose of this study is to determine whether the impact of Social Media Comparison can influence body image formation among young adults, especially Instagram users. This study is a field research with a descriptive qualitative research design. The data collection techniques used in this study were observation, interviews, and documentation. The data analysis technique used in this study is the interactive model approach by Miles & Huberman, which consists of three stages: reduction, data presentation, and conclusion drawing. The results of this study prove that social media comparison can influence and have a significant impact on individuals' views in forming body image and beauty standards as reflected in their thoughts. In terms of positive impacts, social media can serve as a platform for individuals to express themselves and obtain relevant and up-to-date information. However, social media use can also have negative impacts, one of which is social comparison, which can lead to various psychological health disorders such as stress, excessive anxiety, poor body image, feelings of inferiority, and an increased risk of depression, which can lead to other mental disorders that can endanger individual health.